Biotransformation of poly (epsilon-caprolactone) and poly (vinyl chloride) blend - Campos, Adriana de [UNESP]; Franchetti, Sandra Mara Martins [UNESP]; Agnelli, José Augusto Marcondes (Sociedade Brasileira de Microbiologia, 2003)
Poli épsilon-caprolactona é um importante polímero biodegradável e miscível com o PVC, um polímero sintético industrial, termo susceptível e não biodegradável. A blenda PVC/PCL é importante em propriedades mecânicas e biodegradabilidade. Neste trabalho, há indicações que há interação dos microrganismos com a superfície polimérica e esta causa mudanças estruturais na blenda PVC/PCL.

Poly (caprolactone) is a famous biodegradable polymer and miscible with PVC, a commercial synthetic polymer, thermal susceptible and non-biodegradable. This blend is important concerning its mechanical properties and biodegradability. In this work, we testified the biomodification of blend films of PVC/PCL by UV-Vis. spectroscopy. The results show us that there is an interaction between the PVC/PCL film and the microrganisms.
Biotransformação da blenda poli (épsilon-caprolactona) e poli (cloreto de vinila)
Keywords: biotratamento; UV-Vis; blenda PVC/PCL; biotransformação; biotreatment; UV-Vis; PVC/PCL blend; biotransformation